Prevalence and characteristics of incident falls related to nocturnal toileting in hospitalized patients. Issue 2 (4th March 2021) - Decalf, Veerle; Bower, Wendy; Rose, Georgie; Petrovic, Mirko; Pieters, Ronny; Eeckloo, Kristof; Everaert, Karel
ABSTRACT: Objectives : Although nocturia is a risk factor for incident falls in the community, studies are required to gain an understanding of incident falls related to nocturnal toileting in hospitals. The aim of this study is to describe the prevalence and characteristics of incident falls in adult hospitalized patients related to nocturnal toileting. Methods : A retrospective review of the electronic incident reporting and learning system and medical records of inpatients that had an incident fall. Results : The prevalence of toileting-related incident falls was 53% (73/137) and 28% of all incident falls were related to nocturnal toileting. Intravenous fluid infusion was associated with falls related to toileting, whereby median perfusion volume during night-time was 375 ml [IQR: 225–578 ml]. Conclusions : The prevalence of nocturnal toileting-related incident falls in hospitals is high. Nocturia could be a leading cause of these incident falls. Intravenous fluid infusion might be part of the aetiology of (iatrogenic) nocturia.